Sarcoidosis-Associated Pulmonary Hypertension - Shlobin, Oksana A.; Baughman, Robert P. (Seminars in Respiratory and Critical Care Medicine, 2017)
Sarcoidosis-associated pulmonary hypertension (SAPH) is found in 5 to 20% of sarcoidosis patients. Elevated pulmonary artery pressure may be due to multiple factors, including vasculocentric, parenchymal, and mechanical, as well as comorbidities such as cardiac sarcoidosis and sleep apnea. Most SAPH patients have fibrotic lung disease, but SAPH may be present in those without advanced parenchymal lung disease. Several features have been shown to suggest SAPH, including reduced DLCO, shortened 6-minute walk distance, with or without desaturation, and the presence of increased pulmonary artery to aorta ratio on CT scanning. Echocardiography remains an important tool for the evaluation of SAPH but may both over- or underestimate the severity of pulmonary artery pressure. Right heart catheterization remains the definitive test to make the diagnosis. There have been several reports on the value of different modalities of treating SAPH. These include prospective clinical trials and one double-blind placebo-controlled randomized trial. Evidence-based guidelines for treatment of SAPH are discussed in this review.
Keywords: precapillary pulmonary hypertension; bosentan; epoprostenol; echocardiography; right heart catheterization